Eccentric connectivity index of certain classes of cycloalkenes - Haoer, Raad Sehen; Mohd Atan, Kamel Ariffin; Khalaf, Abdul Jalil Manshad; Md. Said, Mohamad Rushdan; Hasni @ Abdullah, Roslan (Springer, 2015)
Let G be a simple connected molecular graph. The eccentric connectivity index ξ(G) is defined as ξ(G)=∑vϵV(G)deg(v)ec(v), where deg(v) denotes the degree of vertex v and ec(v) is the largest distance between v and any other vertex uϵG. In this paper, we establish the general formulas for the eccentric connectivity index of molecular graphs of cycloalkenes.